2017
DOI: 10.1111/1346-8138.13785
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the correlation between severity of acquired idiopathic generalized anhidrosis and quality of life scores

Abstract: Symptoms of acquired idiopathic generalized anhidrosis (AIGA) include heat retention and/or heat stroke due to the effects of the disorder on the perspiration ability of the whole body under thermal environmental changes or exercise. Additionally, cholinergic urticaria can also occur in these patients. AIGA has a major impact on everyday life. However, the effects of AIGA severity on the quality of life (QOL) of the patients have not been sufficiently defined. The objective of this study was to evaluate the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Compared to the impact on QoL caused by other nail disorders or dermatological diseases, we found that the average DLQI score (13.1) in patients with paronychia related to oncologic treatments was much higher than those of patients with psoriatic nails (4.44), chronic urticaria (9.32–9.64), psoriasis (8.36–11.6), dermatomyositis (10.7), pemphigus vulgaris (10.9), chronic hand eczema (5.5–11.1), hyperhidrosis (11.1), acquired idiopathic generalized anhidrosis (11.2) and atopic dermatitis (5.30–11.94), but similar to that of patients with extensive alopecia areata (13.37) . Thus, paronychia related to oncologic treatments may cause significantly impaired QoL in cancer patients.…”
Section: Discussionmentioning
confidence: 79%
“…Compared to the impact on QoL caused by other nail disorders or dermatological diseases, we found that the average DLQI score (13.1) in patients with paronychia related to oncologic treatments was much higher than those of patients with psoriatic nails (4.44), chronic urticaria (9.32–9.64), psoriasis (8.36–11.6), dermatomyositis (10.7), pemphigus vulgaris (10.9), chronic hand eczema (5.5–11.1), hyperhidrosis (11.1), acquired idiopathic generalized anhidrosis (11.2) and atopic dermatitis (5.30–11.94), but similar to that of patients with extensive alopecia areata (13.37) . Thus, paronychia related to oncologic treatments may cause significantly impaired QoL in cancer patients.…”
Section: Discussionmentioning
confidence: 79%
“…We might have waited for spontaneous remission if our patients had only mild symptoms; however, most of our patients had severe symptoms that restricted their activities: 80% of the patients showed severe hypohidrosis/anhidrosis (>75% of body surface area) and 71% had pain (Table 1). 2 Steroid pulse therapy has the potential to relieve such symptoms within a few days 8,15 . The decision to delay therapy must be made only after careful consideration, and the risk of a decreased therapeutic effect must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted 25% as the threshold according to the criteria for scoring disease severity described in the Japanese guideline (area of hypohidrosis or anhidrosis scored as follows: 1, 25%–49%; 2, 50%–74%; and 3, 75%–100%) 1 . This score reportedly has a good correlation with quality of life 2 . In this analysis, we did not consider whether the patients developed recurrence after the therapy; that is, we grouped all of the patients with recurrence as responders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sweat glands are distributed all over the human body, their density is the highest in the armpits, soles, palms and forehead [1]. Perspiration disorders may manifest as increased (hyperhidrosis) or decreased (hypohidrosis/anhidrosis) sweating, and both of these conditions may significantly impair the quality of life [2,3]. In hyperhidrosis (HH) there are many possible methods of treatment, including oral medications (e.g.…”
Section: Introductionmentioning
confidence: 99%